2021
DOI: 10.3390/pharmaceutics13060846
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Modern In Vitro Permeability Methods with the Aim of Investigation Nasal Dosage Forms

Abstract: Nowadays, the intranasal route has become a reliable alternative route for drug administration to the systemic circulation or central nervous system. However, there are no official in vitro diffusion and dissolution tests especially for the investigation of nasal formulations. Our main goal was to study and compare a well-known and a lesser-known in vitro permeability investigation method, in order to ascertain which was suitable for the determination of drug permeability through the nasal mucosa from differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Overall, the PDA1-5 nanoparticle flux diffusions were in the range of picograms per m 2 per second, which indicates that they could not penetrate through the membrane or might penetrate but at a very slow rate. In general, chemicals or drugs that can penetrate the skin should have a transdermal flux within milli-to micrograms per unit area per unit time, such as nitroglycerin, transcutrol, ibuprofen, and ketoprofen. …”
Section: Resultsmentioning
confidence: 99%
“…Overall, the PDA1-5 nanoparticle flux diffusions were in the range of picograms per m 2 per second, which indicates that they could not penetrate through the membrane or might penetrate but at a very slow rate. In general, chemicals or drugs that can penetrate the skin should have a transdermal flux within milli-to micrograms per unit area per unit time, such as nitroglycerin, transcutrol, ibuprofen, and ketoprofen. …”
Section: Resultsmentioning
confidence: 99%
“…The medium in the acceptor chamber is constantly agitated by a magnetic stirring bar (Mattiasson, 2020). Bartos et al (2021) compared the suitability of a vertical diffusion cell apparatus (Franz diffusion cell device) to a horizontal diffusion apparatus (side-by-side type diffusion device) for different formulations (including a spray, gel, and powder). The study found that spray and powder formulations could be investigated by horizontal diffusion devices; however, the investigation of gel formulations is not desirable in this type of diffusion device.…”
Section: Diffusion Chamber Devices For Ex Vivo Permeation Studiesmentioning
confidence: 99%
“…The steady-state flux (Jss, mg/cm 2 /h) was computed from the quantity of EH, which permeated through the nasal mucosa (Q) divided by the membrane surface and the time duration. The permeability coefficient (Kp, cm/h) was calculated from Jss and the initial drug concentration (C 0 ) as given below [29].…”
Section: Apparatus Assemblymentioning
confidence: 99%